Preventing Cancer or Finding a Cure: Which is the Better Approach? - Petrak K (Medical Science: Trends and Innovations Vol. 2, 2025)
The rate of dying from cancer in the US has declined steadily over the past two decades. During the last ten years for which data are available, the rate of new cancer diagnoses decreased by about 2% per year in men and remained about the same in women. Huge resources are being expended in search of cancer therapies, with limited success. Cancer is believed to originate from an irreversible genetic alteration, a part of both normal and abnormal biological processes. It is questionable whether such essential biological behavior can be put under sufficient control to cure cancer. Given that events leading to cancer development appear to be too complex to be successfully manipulated by drug therapies, initiatives to “cure cancer” should be reevaluated and reconsidered, with a likely anticipated conclusion that taking steps to limit cancer initiation might be more cost-effective, and hence focus research efforts on measures to prevent rather than cure cancer. Appropriate steps should be taken vigorously and effectively to remove from our environment (for example, the air, water, and food supply) pollutants identified as initiators and promoters of biological pathways that lead to cancer.